THE ROLE OF SCHOOL LIBRARIANS AS LIAISONS AND OUTREACH FACILITATORS - Setiawan, Dinda Aura; Cahyanti, Fitri Tri; Putrima, Yunidia Ali (Academic Solution Publisher, 2025)
This study examines the role of librarians in fostering collaboration and outreach efforts at the State Elementary School Library No. 101931 Perbaungan, Serdang Bedagai Regency. Librarians function as intermediaries, bridging the library with various stakeholders, including students, teachers, and parents, to enhance their understanding and utilization of information resources. Additionally, outreach librarians play a crucial role in introducing and educating the school community about library services, thereby encouraging greater engagement and utilization of library facilities.This research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation studies. The findings indicate that librarians at SD Negeri No. 101931 Perbaungan actively contribute to strengthening relationships between the library and the school community. Moreover, they implement various initiatives to increase library usage and promote its services to the broader community. The dual roles of librarians as liaisons and outreach facilitators significantly support the educational process in schools and enhance library services.